School beyond school. School space management between resource regeneration and sharing - Filippo Angelucci; Michele Di Sivo; Daniela Ladiana (Techne, 2013)
The instance of existing school asset care, maintenance and regeneration represents the opportunity to develop some researches based on an model for an integrated management of the maintenance of learning spaces quality and efficiency, in order to re-think and modify them as “shared urban strategic resources” through which directly to involve the users operating both in schools and in neighbourhoods. An intervention philosophy has therefore emerged, based on the principle of ‘resilience’ within the school-city macrosystem: a complex system where technological, ecological and social elements co-exist and co-evolve within a vision linking the resource preservation culture with the living sustainability culture.